2015
DOI: 10.1136/sextrans-2015-052010
|View full text |Cite
|
Sign up to set email alerts
|

The incidence ofTrichomonas vaginalisinfection in women attending nine sexually transmitted diseases clinics in the USA: Table 1

Abstract: Objectives Trichomoniasis (TV) is associated with an increased risk of acquisition of sexually transmitted diseases (STDs) and HIV. The purpose of this study is to evaluate factors associated with incidence TV among female STD clinic attendees in the USA. Methods Data were collected from women participating in a randomised controlled trial evaluating brief risk reduction counselling at the time of HIV testing to reduce sexually transmitted infections (STIs) incidence in STD clinics. Participants recruited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
(24 reference statements)
1
10
1
Order By: Relevance
“…No case of trichomoniasis was detected. In contrast, the prevalence of C. trachomatis in the STD attendees was 16%, which is higher than the rates of 3.8-8.6% reported from studies at STD clinics in Western and Northern Europe, the USA and Australia, where women were tested for both T. vaginalis and C. trachomatis (2,4,6,9). This is not surprising, as the prevalence of diagnosed C. trachomatis infections in Iceland for the past 20 years has been among the highest in Europe, or up to 739 cases per 100,000 population (http://www.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…No case of trichomoniasis was detected. In contrast, the prevalence of C. trachomatis in the STD attendees was 16%, which is higher than the rates of 3.8-8.6% reported from studies at STD clinics in Western and Northern Europe, the USA and Australia, where women were tested for both T. vaginalis and C. trachomatis (2,4,6,9). This is not surprising, as the prevalence of diagnosed C. trachomatis infections in Iceland for the past 20 years has been among the highest in Europe, or up to 739 cases per 100,000 population (http://www.…”
Section: Discussioncontrasting
confidence: 67%
“…Thus, nucleic acid amplification tests (NAATs), with a sensitivity and specificity of 95-100% (1), have revolutionized the diagnosis of trichomoniasis and are providing new insights into the epidemiology of the disease. Recent NAAT-based studies on women attending sexually transmitted diseases (STD) clinics have shown unexpectedly high prevalence rates (14.6-27%) of trichomoniasis in the USA (2,3). In contrast, the prevalence in Western European countries and Australia appears to be substantially lower, i.e.…”
mentioning
confidence: 99%
“…Specifically, we found 14.6% of N.gonorrhoeae, 13.2% of T.vaginalis, and 12.1% of C.trachomatis. Our study findings were similar to the results reported in a study of women attending STD clinics in the USA, with the exception of N.gonorrhoeae, which was four times greater in our study [17]. Among domestic investigations, a study by B. Khandsuren et al found the prevalence of C.trachomatis at 39.3% among individuals with signs of urogenital tract inflammation, while a study by Erdenechimeg.Ch reported a 34.1% prevalence rate [18,19].…”
Section: Discussionsupporting
confidence: 80%
“…In studies representative of the general population, the rates of trichomonas, chlamydia, and gonorrhea infections have been estimated at 3.2, 2.2, and 0.2%, respectively (1,2). Prevalence estimates among women seeking family planning and sexual health care range from 7.5 to 25% (3,4). Globally, trichomonas infections account for nearly half of all curable STIs.…”
mentioning
confidence: 99%